Escherichia coli strain with a deletion of the chromosomal ampC gene marked with TcR, suitable for production of penicillin G acylase - Vizváryová, M; Stuchlík, S; Grones, J; Macor, M; Turna, J (Folia microbiologica, 1999)
Escherichia coli strain which contains a marker of tetracycline resistance gene (TcR) placed by P1 transduction beside the chromosomal deletion of ampC gene (delta ampC) coding for beta-lactamase was constructed. Such introduction of TcR marker permits a fast and simple selection for the transfer of delta ampC by P1 transduction into industrial E. coli strains. This approach was used for constructing an E. coli strain suitable for penicillin acylase production.
Keywords: bakteriální geny; Bacteriophage P1; rekombinantní proteiny; beta-Lactamases; Escherichia coli; Penicillin Amidase; plazmidy; Bacterial Proteins; bakteriální proteiny; genetické markery; Gene Deletion; Plasmids; Recombinant Proteins; Tetracycline Resistance; transdukce genetická; Genetic Markers; delece genu; rezistence na tetracyklin; Transduction, Genetic; beta-laktamasy; bakteriofág P1; penicilinamidasa; Genes, Bacterial